The Implementation of E-Governance Initiatives Plays a Crucial Role in Ensuring the Realization of a Digital Bangladesh - Rahman, Mahmudur (Journal of Public Representative and Society Provision, 2023)
The ideas of e-governance and Digital Bangladesh are intricately interconnected. E-governance pertains to the utilization of information and communication technology (ICT) with the aim of enhancing the provision of government services to the general populace. Digital Bangladesh, on the other hand, is a vision for a technologically advanced society where ICT is used to foster a knowledge-based environment and improve the lives of all citizens. The implementation of e-governance initiatives plays a crucial role in ensuring the realization of a Digital Bangladesh. By providing citizens with convenient and efficient access to government services online, e-governance can help to reduce corruption, improve transparency, and promote accountability. It can also help to bridge the digital divide and make government services more accessible to all citizens, regardless of their location or socioeconomic status. In order to realize Digital Bangladesh, the government of Bangladesh is dedicated to e-governance. A number of e-governance initiatives have already been implemented, such as the National Portal, the Digital Center Network, and the One Stop Service (OSS) Centers. These initiatives have made it easier for citizens to access a wide range of government services online, such as paying taxes, applying for passports, and registering businesses. Nevertheless, certain obstacles must be confronted to effectively achieve the goal of Digital Bangladesh. One challenge is the lack of digital literacy among a large section of the population. Another challenge is the need to improve the reliability and affordability of internet access. Furthermore, it is essential to devise and execute e-governance initiatives that are customized to cater to the distinct requirements of various segments of the population, including those experiencing poverty, the elderly, and those with disabilities. Despite the challenges, the government of Bangladesh is making significant progress in the implementation of e-governance and the realization of Digital Bangladesh. The adoption and execution of e-governance projects are significantly benefiting both individuals and companies across the nation. The primary objective of this study is to examine the many programs and efforts implemented by the Government of Bangladesh in its pursuit of establishing Digital Bangladesh. To conduct a comprehensive and thorough study, the following goals have been identified: To get information about the initiatives. To analyze the roles of the programs.